STUDENT TEACHERS ASK: ARE WE WORKERS OR COLLEAGUES? - Keleşoğlu, Serkan; Yetkiner, Alper (International Online Journal of Education and Teaching, 2021)
The Teaching Practice Course is the most important course for prospective teachers to gain professional qualifications. This course will be able to achieve its goals through the healthy communication that mentor teachers will establish with the prospective teachers. This research focuses on the communication and interaction between prospective and mentor teachers. The purpose of the research is to determine how the prospective teachers interpret the relationship between the two stakeholders. For this purpose, phenomenological research, was carried out. In two different universities and in different branches of Turkey joining the 35 prospective teachers teaching practice course with focus group interviews were made at different times. The interview texts examined by two different experts were subjected to descriptive analysis. In the study; some prospective teachers think that they do not consider the mentor teachers professionally adequate and experience professional burnout; were seen as colleagues by the mentor teachers, while others were concluded that they thought they were perceived or ignored as assistants. Prospective teachers stated that in order for this process to be more effective, they should be perceived as colleagues by the mentor teacher and that the teaching staff should participate more actively in the process.